Investigating the follow-up discontinuation among people living with HIV in North Shoa Zone, Oromia, Ethiopia - Amhare, Abebe Feyissa; Goyomsa, Girma Garedew; Al Issa, Yasmeen Moshtaq A. (Frontiers in Public Health, 2024)
Introduction Follow-up discontinuation among people living with HIV can increase mortality and HIV spread within communities. This study investigates the impact of the COVID-19 on follow-up discontinuation among people living with HIV in Ethiopia. Methods This longitudinal study used retrospective document review to compare follow-up status of people living with HIV during the COVID-19 pandemic with their status from 2017 to 2019. Data from selected health facilities were collected using a checklist, entered and cleaned in Excel, and analyzed in Stata. Descriptive statistics were presented in tables and line graphs. Incidence risk (IR) and incidence rate ratios (IRR) were calculated. Results Between 2017 and 2021, a total of 7,447 people living with HIV were registered to begin ART at selected health facilities. Annual retention rates were consistent from 2017 to 2019, ranging from 0.941 to 0.949. During the COVID-19 pandemic, they dropped to 0.837 in 2020 and 0.840 in 2021. Retention rates were significantly correlated with loss to follow-up (r: −0.959, p ≤ 0.001), death (r: −0.968, p ≤ 0.001), and transfer-out (r: −0.979, p ≤ 0.001). Moreover, the incidence of loss to follow-up (IRR: 3.00, 95%CI: 2.71–3.33, p ≤ 0.001), death (IRR: 3.61, 95%CI: 3.13–4.16, p ≤ 0.001), poor adherence (IRR: 2.27, 95%CI: 2.14–2.40, p ≤ 0.001), and severe malnutrition (IRR: 2.32, 95%CI: 2.18–2.47, p ≤ 0.001) significantly increased during the COVID-19. Conclusion The study found that COVID-19 healthcare disruptions increased follow-up loss among people living with HIV and heightening the disease burden in Ethiopia.